Acute otitis media associated bilateral sudden hearing loss: case report and literature review. (17th April 2017) - Smith, A; Gutteridge, I; Elliott, D; Cronin, M
Abstract: Background: Sudden sensorineural hearing loss is a rare otological condition with potential for dire outcomes including permanent hearing loss. Although the majority of cases are deemed idiopathic, bilateral sudden sensorineural hearing loss represents a rare subset typically related to systemic conditions, with higher morbidity and mortality. A controversial association with acute otitis media has been reported, with few bilateral cases published in the literature. Case report: A very rare case of bilateral sudden sensorineural hearing loss associated with acute otitis media is described, with a review of the literature. Conclusion: The limited evidence available suggests that acute otitis media with tinnitus and/or bacterial pathology may have an increased risk of sudden sensorineural hearing loss, which is consistent with the case described. Although there is no sufficiently powered published evidence to provide definitive treatment guidelines, the literature reviewed suggests that early myringotomy and antibiotics may greatly improve treatment outcomes.